Unveiling public sentiment towards misogynism in the film a slightly different in X - Wildan Alfarizi; Gema Nusantara Bakry (Master of Communication Science Program, Universitas Diponegoro, 2025)
After a few weeks of the airing of the movie “Agak Laen”, a lot of people are discussing about the topics of misogyny in this movie on X or what used to be known as Twitter. This study aims to analyze the communication network and public sentiment towards the topic of misogyny in the film “Agak Laen” on X social media platform. Through the Social Network Analysis (SNA) method with a descriptive quantitative approach, researchers identified the communication as well as interaction patterns among social media users. Then, researchers collected the data using Tweet-Harvest with a Twitter connection using Tweet Auth and analyzed the obtained data using a python programming language built on the Google Colab platform. Afterwards, researchers processed the data using Gephi version 0.10.1 and Netlytic. The results of sentiment analysis towards 55 Tweets showed the majority of neutral sentiments, indicating that public discussions related to the topic of misogynism in the film “Agak Laen” tended to be less emotionally intense. The research also found that the X-user account @runiarumndari served as the key actor with the most interactions